Intraoperative sub-tenon injection increases optic nerve length transection during enucleation - Natta Sakolsatayadorn (2018)
PURPOSE:: To determine the effect of sub-Tenon injection on the length of optic nerve resected during enucleation. METHODS:: Case-control laboratory study on 22 orbits of 11 unpreserved, fresh-frozen human cadavers. Each cadaver underwent a conventional enucleation technique on one side and an otherwise identical technique on the contralateral side that included sub-Tenon injection of 2.5 ml normal saline in each oblique quadrant. Resected optic nerve lengths were measured and compared using Student t tests. RESULTS:: The mean optic nerve length was 15.2 mm (range, 5.0-21.0 mm) in the sub-Tenon injection group and 11.3 mm (range, 5.0-19.0 mm) in control group (p = 0.015). CONCLUSIONS:: Sub-Tenon injection during enucleation allows for significantly longer optic nerve resection lengths in unpreserved, fresh-frozen human cadavers. © 2013 The American Society of Ophthalmic Plastic and Reconstructive Surgery, Inc..